Active enhancers strengthen insulation by RNA-mediated CTCF binding at chromatin domain boundaries - Islam, Zubairul; Saravanan, Bharath; Walavalkar, Kaivalya; Farooq, Umer; Singh, Anurag Kumar; Radhakrishnan, Sabarinathan; Thakur, Jitendra; Pandit, Awadhesh; Henikoff, Steven; Notani, Dimple (Genome Research, 2023)
Vertebrate genomes are partitioned into chromatin domains or topologically associating domains (TADs), which are typically bound by head-to-head pairs of CTCF binding sites. Transcription at domain boundaries correlates with better insulation; however, it is not known whether the boundary transcripts themselves contribute to boundary function. Here we characterize boundary-associated RNAs genome-wide, focusing on the disease-relevant INK4a/ARF and MYC TAD. Using CTCF site deletions and boundary-associated RNA knockdowns, we observe that boundary-associated RNAs facilitate recruitment and clustering of CTCF at TAD borders. The resulting CTCF enrichment enhances TAD insulation, enhancer–promoter interactions, and TAD gene expression. Importantly, knockdown of boundary-associated RNAs results in loss of boundary insulation function. Using enhancer deletions and CRISPRi of promoters, we show that active TAD enhancers, but not promoters, induce boundary-associated RNA transcription, thus defining a novel class of regulatory enhancer RNAs.
10.1101/gr.276643.122